Development and validation of the social reward questionnaire–early childhood - Godfrey, KJ; Foulkes, L; McMorris, C; Harris, AD; Bray, S (American Psychological Association, 2022)
Social interactions like group inclusion, receiving praise, or treating others kindly can be motivating and enjoyable. Social reward sensitivity, including motivation and enjoyment, varies between individuals. In early childhood, this variation may relate to differences in social experience and development. Social reward questionnaires have been developed to measure individual differences in social enjoyment for adolescents and adults, but no early childhood measure currently exists. Here, we describe the development and validation of the parent/caregiver report Social Reward Questionnaire-Early Childhood (SRQ-EC) for children aged 3-7 years. The SRQ-EC was developed to quantify both wanting (motivation) and liking (enjoyment) of social rewards, which were considered in separate factor models. For wanting and liking models, exploratory (N = 126) and confirmatory (N = 344) factor analyses identified that three subscales best represented early childhood social reward sensitivity, which were: Sociability (large groups), Admiration (praise and positive attention), and Prosocial Interactions and Compliance (kindness and rule following). SRQ-EC subscales were internally consistent (ω = 0.76-0.91, α = 0.75-0.88, mean interitem correlations = 0.38-0.60) with high test-retest reliability over 2-weeks (r = 0.66-0.85, all p < .001). Subscales differentially associated with other social behavior and personality measures, suggesting construct validity. SRQ-EC subscale scores further showed differential and significant associations with autistic-like traits in nonautistic children. These results suggest that SRQ-EC subscale scores are reliable for assessing social reward sensitivity during early childhood, which could offer key developmental insight regarding interindividual variation in early social behavior.